Global trade and health: an Indonesian perspective on the asean medical device directive policy - Nurul Hidayati; Dedy Almasdy; Abdi Setya Putra (Berita Kedokteran Masyarakat (BKM), 2021)
Purpose: Health care equipment international trade could serve a new strategic revenue for Indonesia. Since its implementation in 2015, AFTA has been a very strategic issue in creating export opportunities for its member countries. One of the sectors that becomes a priority for ASEAN integration is in the field of medical devices which is regulated in the ASEAN Medical Device Directive (AMDD) policy. Indonesia itself has officially ratified AMDD policy since 2018, but Indonesia will have been facing the problem of quality, innovation and diversification of medical devices. This study examines the competitiveness opportunities for domestic medical devices in ASEAN Free Trade Area. Method: This study used a qualitative method where information was obtained from in-depth interviews and document review. The informants came from policy makers, implementing officers, and stakeholders. Results: Indonesia has harmonized 26 out of 31 standards mandated by AMDD. Conformity assessment bodies in Indonesia that have been certified by the National Accreditation Committee have received international recognition. Indonesia has many potential exporting innovative medical devices to ASEAN countries. Fulfillment of medical devices is carried out through compulsory licensing and parallel import mechanism.